Description Of Hemoglobin Levels And Blood Pressure In Security After Night Picket Lines - Getas, I Wayan; Oktapia, Selfi Tri (Jurnal Analis Medika Biosains (JAMBS), 2025)
Night shift security can negatively affect the body's condition because activities carried out at night will reduce the amount of rest the body needs. Reduced rest will have an impact on decreased hemoglobin levels and increased blood pressure or decreased blood pressure. Rest at night is very important because the detoxification process of cell regeneration and the formation of red blood cells usually occurs at night. Objective: To find out the picture of hemoglobin levels and blood pressure on security after night picket. Methods: This study is observational with cross sectional method using purposive sampling technique with a total of 44 respondents. Analysis of results can be obtained descriptively by looking at Hb levels and blood pressure. Results: The results of blood pressure checks on security after night pickets with an average of 145/85 and the highest blood pressure is 201/110 mmHg there are 25 people (57%), the lowest blood pressure check results 114/70 mmHg There are 19 people (43%). For the results of the examination of hemoglobin levels in security after night picket hemoglobin levels with an average of 14.1 and the highest hemoglobin is 17.4 g/dL and normal blood pressure there are 32 people (73%), the lowest hemoglobin level examination results 11.4 g/dL there are 12 people (27%). Conclusion: Night picketing can increase blood pressure and reduce hemoglobin levels in security.